Optimalisasi Memori dalam Pembelajaran Bahasa Arab: Kajian Neuropsikolinguistik : Indonesia - Siti Amelia Sriyono; Abdul Kahfi Amrulloh; Zainal Arifin Ahmad; Dwichandra Setyorini (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
Learning Arabic for non-Arabic speakers faces complex linguistic, cognitive, and affective challenges, particularly related to working memory limitations, cognitive load, and difficulties in retaining vocabulary and linguistic rules. Differences in the phonological, morphological, syntactic, and writing systems of Arabic often complicate the process of encoding and storing information in long-term memory. Therefore, learning strategies that optimize memory function and strengthen learners' memory are needed. This study aims to examine the role of mnemonic method and multisensory approach in strengthening memory in Arabic language learning. The method used is a narrative review of scientific articles from 2020 to 2025 obtained through Google Scholar and ResearchGate. The results show that mnemonic techniques—such as rhymes, acronyms, keywords, and chunking—are effective in helping to encode, store, and recall Arabic language information, especially vocabulary and grammar. In addition, a multisensory approach involving visual, auditory, and kinesthetic components has been proven to enrich the information encoding process, increase learning motivation, and strengthen material retention. The integration of mnemonic method and multisensory learning contributes significantly to creating Arabic language learning that is more effective, engaging, and adaptive to the memory mechanisms of learners.